2009
DOI: 10.1021/ja900531f
|View full text |Cite
|
Sign up to set email alerts
|

Nature of Molecular Interactions of Peptides with Gold, Palladium, and Pd−Au Bimetal Surfaces in Aqueous Solution

Abstract: We investigated molecular interactions involved in the selective binding of several short peptides derived from phage-display techniques (8−12 amino acids, excluding Cys) to surfaces of Au, Pd, and Pd−Au bimetal. The quantitative analysis of changes in energy and conformation upon adsorption on even {111} and {100} surfaces was carried out by molecular dynamics simulation using an efficient computational screening technique, including 1000 explicit water molecules and physically meaningful peptide concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

35
446
7
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 333 publications
(489 citation statements)
references
References 56 publications
35
446
7
1
Order By: Relevance
“…This local minimum is related to the 'solvent mediated' adsorption of the AAs, where the AA is separated from the graphene interface by the first layer of interfacial water molecules. This 'solvent mediated' minimum has also been observed for the adsorption of AAs and peptides at metal interfaces, 18,78,79 particularly for silver, 18,80 and mineral 26,30 interfaces.…”
Section: Adsorption Free Energy Of Amino Acidsmentioning
confidence: 58%
“…This local minimum is related to the 'solvent mediated' adsorption of the AAs, where the AA is separated from the graphene interface by the first layer of interfacial water molecules. This 'solvent mediated' minimum has also been observed for the adsorption of AAs and peptides at metal interfaces, 18,78,79 particularly for silver, 18,80 and mineral 26,30 interfaces.…”
Section: Adsorption Free Energy Of Amino Acidsmentioning
confidence: 58%
“…Similar diversity of surface environments is also expected for other oxides such as titania and apatites, however, not for precious metals that are of simple chemistry and attract similar peptide sequences. [77][78][79][80][81][82][83] Two major factors play a role for the construction of a silica surface model. One is the type of substrate that determines the area density of silanol groups; the other is the degree of ionization ( as a function of pH and ionic strength.…”
Section: A Silica Surface Model Databasementioning
confidence: 99%
“…Previous simulation studies have indicated that the adsorption of molecules at different facets can differ. 29,31,37,38,41 For example, the aforementioned study of Wright et al…”
mentioning
confidence: 99%